Academic Stress Levels in Junior High School Students During Covid-19 Online Learning - Ines Rahayu (Inovan Publisher, 2024)
Academic stress levels in junior high school students during online learning due to COVID-19. The purpose of this study was to examine the level of academic stress in junior high school students in Kedepatian Semerap. This study used a quantitative method with descriptive analysis. The population in this study was all junior high school students in Kedepatian Semerap, with a sampling technique using accidental sampling with a total of 63 participants. The results showed that the level of academic stress in junior high school students during online learning was in the moderate category.